Associations of Circulating Gamma-Linolenic Acid and Cardiometabolic Health in Chinese Adults: A Prospective Study - Yu-Ming Chen; Hai-Li Zhong; Yan Yan; Ying-Di Yang; Hang-Zhu Chen; Ting-Yu Sun (Proceedings)
Background: Previous studies have shown that dietary and circulating n-6 polyunsaturated fatty acids (n-6 PUFAs) have beneficial associations with cardiometabolic health in humans. However, some studies showed inconsistent associations between circulating gamma-linolenic acid (GLA, C18:3 n-6), a metabolite of linoleic acid (LA, C18:2 n-6), and cardiometabolic health compared to LA. Therefore, this study aimed to examine the associations of erythrocyte GLA proportions with the presence and incidence of cardiometabolic diseases in Chinese adults. Methods: This prospective study included 3591 participants (40–80 years) from the Guangzhou Nutrition and Health Study, South China. The participants were recruited from 2008 to 2013 and followed up every 3 years. Erythrocyte fatty acids were determined using the baseline samples. Assessments of metabolic syndrome (MetS), carotid intima-media thickness, blood lipids, and questionnaire interviews were conducted at each visit. The associations between erythrocyte GLA and the presence and incidence of MetS, carotid artery plaque (CAP), and coronary heart diseases (CHD) were analyzed using logistic and Cox regression models after adjusting for potential covariates. Results: Among the 3591 participants at baseline, 1155, 941, and 417 had MetS, CAP, and CHD, which were included in the cross-sectional analyses. After a median of a 9-year follow-up, 935/2436, 1172/2203, and 524/2507 participants (case N/total N followed up) developed MetS, CAP, and CHD and were included in the prospective analyses, respectively. Multivariate-adjusted odds ratios (ORs) and 95% confidence intervals (95% CIs) of MetS, CAP, and CHD for the quartile (Q) 4 (vs. 1) of GLA were 3.11 (2.50, 3.87), 1.25 (0.99, 1.58), and 1.54 (1.12, 2.13) (all p-trends < 0.05). The corresponding hazard risks (HR) and 95% of the CIs of the 9-year incidences were 1.45 (1.20, 1.75), 1.25 (1.06, 1.48), and 1.40 (1.10, 1.80) (all p-trends < 0.05), respectively. However, LA showed beneficial associations with MetS presence (Q4 vs. Q1, OR: 0.65, 95% CI: 0.53, 0.80) and the 9-year CAP incidence (Q4 vs. Q1, HR: 0.78, 95% CI: 0.66, 0.92) (p-trends < 0.01). Conclusions: Our findings show a detrimental association between erythrocyte GAL and the presence and incidence of MetS, CAP, and CHD in Chinese adults. Experimental studies are needed to confirm the causal relationship.